Dredging Analysis at Makassar New Port - Umar, Hasdinar; Ashury, Ashury; Ayyub, Muhammad (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2023)
Dredging is used to create new harbors, berths, or waterways, or to deepen existing facilities to allow vessels with heavy drafts to access them. The dredging analysis at Makassar New Port aims to calculate how much the dredging volume. With this data, research can be used as a source of reference and consideration for researchers and port authorities. The research method is descriptive, where the primary data is data obtained based on direct observation at the research location, while secondary data is data that is researched and collected by related parties. Then an analysis is carried out to calculate the volume of dredging at Makassar New Port. From the results of the analysis, it can be concluded that dredging was carried out with a dredge volume reaching 1,953,764.47 m3, with a processing time of 349 days.